Learning Strategies for Survival Adaptation of Mo Lam Entrepreneurs during COVID-19 Pandemic - Thitisak Wechkama (Journal of Educational Issues, 2024)
This research aimed to investigate learning strategies for survival adaptation and develop guidelines for Mo Lam entrepreneurs. Qualitative research was employed by collecting data through interviews and group discussion, including the band’s owners and executives, the band’s members, musicians, performers, and audiences. The learning successful of Mo Lam business owners were; confident in their performance ability, creative and capable of using technology in their performances, determined to work hard to achieve targets, and involved at all steps of the planning. Concerning the factors for successful survival strategies, the entrepreneurs reported having used various techniques to help them accommodate the need to surviving. By pressing the like and share buttons, online viewers help spread the brand’s name. Money transfers were sparked by the internet Mo Lam business, which reduced business costs and made material movement easier. Furthermore, the web business aided in the prevention of epidemics by allowing audiences to communicate with one another. Most crucially, online performance enabled entrepreneurs to generate company returns with minimal expenditure, while crime and conflict rates were theoretically reduced as a result of online performances.